Methods of reconstruction of perineal wounds after abdominoperineal resection. Literature review - S. S. Gordeev; V. A. Ivanov; D. V. Kuz'michev; R. I. Tamrazov; A. O. Rasulov (Тазовая хирургия и онкология, 2017)
The problem of wound closure after abdominoperineal resection to treat oncological diseases remains unsolved. Formation of a primary suture in the perineal wound can lead to multiple postoperative complications: seroma, abscess, wound disruption with subsequent perineal hernia. Chemoradiation therapy as a standard for locally advanced rectal or anal cancer doesn’t improve results of treatment of perineal wounds and increases duration of their healing. Currently, surgeons have several reconstructive and plastic techniques to improve both direct and long-term functional treatment results. In the article, the most common methods of allo- and autotransplantation are considered, benefits and deficiencies of various techniques are evaluated and analyzed.